Effect of Deformed and Plain Rebars on the Behavior of Lightly Reinforced Boundary Elements - Mohammad Ali Pourakbar; Saeed Tariverdilo (Journal of Rehabilitation in Civil Engineering, 2020)
In recent earthquakes common failure modes of lightly reinforced shear walls includes rebar fracture and out of plane buckling of boundary elements. In latest edition of ACI 318 and also latest amendment of NZS 3101-2006 to avoid rebar fracture in boundary elements, minimum longitudinal reinforcement ratio is increased. This experimental study investigates that rather than increasing the reinforcement ratio, is it possible to avoid rebar fracture by use of plain rebars in the critical sections of boundary elements in lightly reinforced shear walls. Experimental program includes specimens with plain and deformed rebars tested under monotonic and cyclic loading. Strain profile of the rebars are evaluated employing correlation between hardness and residual strain. Results indicate that failure of specimens with plain rebars occurs on single crack, however they have more uniform strain profile. On the other hand, in the specimens with plain and deformed rebars, out of plane buckling occurs at same crack width, but different elongations. It is shown that local strain demand (crack width) has better correlation with out of plane buckling in comparison with average axial strain.